Economic value of Ukrainian steppe bees - Гречка, Г. М. (Scientific Progress & Innovations, 2013)
The experimental data of comparative evaluation of purebred bee of Ukrainian steppe breed with local families according to a result of accounting grown bee brood in different periods of their active life, bee collected pollen, produced honey and rebuilt honeycombs are given. Judging from the average number of grown bee brood, the intensity of development in the bee families of Ukrainian steppe breed by 28.7% more than in families with local female bees. Bringing up a sufficient number of worker bees, pure-bred bees provide high productivity for honey collection. Ukrainian steppe bees collected more than 19.6% of bee pollen, 33.4% of honey and rebuilt more than 20.2% of honeycombs.